Penerapan Asas Peradilan Sederhana, Cepat, dan Biaya Ringan Dalam Pemeriksaan Tindak Pidana Penganiayaan Dimasa Pandemi COVID-19 - Ruth Gracia Imanuela Matrutty; Juanrico Alfaromona Sumarezs Titahelu; Julianus Edwin Latupeirissa (Faculty of Law, Universitas Pattimura, 2022)
Introduction: This article analyzes the law enforcement process and the application of simple, fast, and low-cost judicial principles in criminal acts of persecution during the COVID-19 pandemic at the Ambon District Court. Purposes of the Research: The purpose of this article is to know the law enforcement process and the application of judicial principles are smple, fast, and low-cost in examining criminal act of persecution during the COVID-19 pandemic at the Ambon District Court.Methods of the Research: The method of research used is normative juridicial, with a problem approach, namely the statute approach, conceptual approach and case approach.Results of the Research: The results of the study found that the law enforcement process for the criminal act of persecution before the COVID-19 pandemic and during the COVID-19 pandemic was in accordance with the applicable laws and regulations. However, in the application of simple, fast, low-cost judicial principles in the case examination process, there is a difference, namely before COVID-19 the examination process was carried out quickly. Meanwhile, during the COVID-19 pandemic, the examination process was quite long because of the obstacles faced such as the absence of witnesses, signal interference, the schedule of court hours that were not on time, the lack of availability of courtroom facilities and infrastructure, the inconvenience of law enforcement officers regarding the application of health protocols due to congestion breath.